Insiders versus Outsiders in Monetary Policy-Making - Timothy Besley; Neil Meads; Paolo Surico (Bank of England, External Monetary Policy Committee Unit, 2007)
This paper looks at the voting patterns of internal and external members of the MPC to investigate how far there are differences between insiders and outsiders. We make three contributions. First, we assess the extent to which the Bank of England internally generated forecasts explain the MPC members' voting decisions. This is important as generating forecasts on a quarterly basis is a key part of the process used by the Bank of England. The forecast for inflation is made public in the Inflation Report while the output gap forecast is not. Second, we use a random coefficient method of estimation in which the parameters of the interest rate rule are allowed, but not required, to be different across members. Third, we find evidence of some heterogeneity in the intercept, a measure of experience on the MPC and the interest rate smoothing parameter, but no significant differences in the members' reaction to the forecasts of inflation and the output gap.
Keywords: D78; E52; 330; Monetary Policy; Voting Patterns; Zentralbank; Führungsorganisation; Geldpolitik; Gruppenentscheidung; Qualifikation; Inflationserwartung; Großbritannien